Racial/Ethnic Disparities in Longitudinal Trajectories of Community Integration After Burn Injury. (July 2020) - Pierce, Bradford S.; Perrin, Paul B.; Pugh, Mickeal; Cariello, Annahir N.; Henry, Richard S.; Sutter, Megan E.; Wiechman, Shelley A.; Schneider, Jeffrey C.
Abstract: Objectives: The aim of this study was to examine potential racial/ethnic disparities in community integration for the 2 yrs after burn injury. Design: A sample of 1773 adults with burn injury from the Burn Model Systems database was used with data on community integration collected at discharge (preinjury recall), 6, 12, and 24 mos after discharge. Methods: Four sets of hierarchal linear models determined the most appropriate model for understanding racial/ethnic differences in Community Integration Questionnaire trajectories over time. Results: Data indicated a decrease in community integration between discharge and 6 mos, a slight increase between 6 mos and 1 yr, and then a plateau between 1 and 2 yrs. White individuals had higher community integration score trajectories over time than black ( b = 0.53, P < 0.001) and Hispanic ( b = 0.58, P < 0.001) individuals, and community integration scores were similar between black and Hispanic individuals ( b = −0.05, P = 0.788). These racial/ethnic disparities remained after accounting for age, sex, total burned surface area, number of days in rehabilitation, and active range of motion deficits. Conclusions: Additional rehabilitation resources should be targeted to helping black and Hispanic individuals integrate back into their communities after burn injury.